Some Actual Aspects of the Methodology of Jurisprudence in the Newly Independent States of Eurasia - Narman Myrzachmetovich Sadykov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article highlights relevant aspects of research methodology in the field of legal science of the newly independent states of Eurasia. The author draws attention to the need to study the historical experience of the development of the theory of state and law in Russia and to update its application in the reform of state-legal system of the newly independent states of Eurasia. Special attention should be paid to the methodology of the research.